Interseksi Indentitas Perempuan: Analisis Cerpen Clara Atawa Wanita yang Diperkosa Karya Seno Gumira Ajidarma - W Winarti (BUANA GENDER : Jurnal Studi Gender dan Anak, 2020)
Individual cannot be described by taking one single category because basically every individual has multiple identity. There is no single identity will ever be found in men or women. There will be an intersection between sex and other social categories such as social class, age, race, ethnicity, religion, education, skin color, and other categories not yet mentioned. Intersection is an approach explaining that every human never has a single identity. People carry their identity and other aspects that actually construct the intersection as a combination of the identity they have. Intersection is something liquid and influenced by both internal and external aspects as well. Internal aspects are the identity carried by the subjects, while external aspects are the contexts of place, time, power relations, and momentum. In Clara Atawa Wanita yang Diperkosa short story by Seno Gumira Ajidarma, the researcher found an intersection of identity had by female main character, Clara. This intersection is formed by three things, they are sex, ethnicity, and social class. These three things cannot be separated as they have formed a single unity refering to the identity of Clara. The intersection occurs because the barriers between the categories of identity are opened. The rape experienced by Clara in this story is not a rape by sex, but a form of oppression to certain ethnicity (Chinese) and social class.